Locating Minimal Fault Interaction in Combinatorial Testing. (29th May 2016) - Zheng, Wei; Wu, Xiaoxue; Hu, Desheng; Zhu, Qihai
Abstract : Combinatorial testing (CT) technique could significantly reduce testing cost and increase software system quality. By using the test suite generated by CT as input to conduct black-box testing towards a system, we are able to detect interactions that trigger the system's faults. Given a test case, there may be only part of all its parameters relevant to the defects in system and the interaction constructed by those partial parameters is key factor of triggering fault. If we can locate those parameters accurately, this will facilitate the software diagnosing and testing process. This paper proposes a novel algorithm named complete Fault Interaction Location (comFIL) to locate those interactions that cause system's failures and meanwhile obtains the minimal set of target interactions in test suite produced by CT. By applying this method, testers can analyze and locate the factors relevant to defects of system more precisely, thus making the process of software testing and debugging easier and more efficient. The results of our empirical study indicate that comFIL performs better compared with known fault location techniques in combinatorial testing because of its improved effectiveness and precision.